Syrian hamster embryo cell lines useful for detecting transforming genes in mouse tumours: detection of transforming genes in X-ray-related mouse tumours. - Sasai, H. (Nature Publishing Group, 1993)
The Syrian hamster embryo cell lines, SHOK and MC-1, were used as recipient cells for DNA transfection assay to detect transforming genes in experimental mouse tumours. A mouse repeat sequence was utilised to check whether each transformed focus included mouse genomic DNA in the Hamster background. We investigated five mouse tumours that are related to X-ray radiation, and detected activated c-K-ras, c-mos, and c-cot oncogenes which induced foci of hamster cells. These results show that SHOK and MC-1 cells have unique properties for detecting transforming genes in experimental mouse tumours. IMAGES: